Manajemen Pemasaran dan Pentingnya Sosial Media untuk Produk UMKM Pondok Pesantren Assyifa Kecamatan Parung Bogor - Amalia, Nurul; Ghifari, Sangkala Wiri; Salsabiil, Kintan Putri; Erwindo, Erwindo; Arianto, Nurmin; Sudaryana, Yayan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The community service project titled “Marketing Management and the Importance of Social Media for MSME Products at Pondok Assyifa Parung, Bogor” aims to enhance the marketing quality of Micro, Small, and Medium Enterprises (MSMEs) at Pondok Pesantren Assyifa Parung, Bogor. This community service is crucial because MSMEs play a central role in economic development. However, they often face various challenges, such as ineffective marketing management and low production skills. This activity is designed to provide training and practical knowledge on effective marketing management through methods including direct mentoring, lectures, simulations, and discussions. The goals of this activity are to improve marketing skills among MSMEs, provide understanding of good marketing management practices, and prepare them for recruiting employees that meet business needs. Through this approach, it is hoped that the participants of the MSME forum at Pondok Pesantren Assyifa in Parung, Bogor will better understand and apply appropriate marketing strategies.